Xenon as a Potential Enhancer of Hypoxic Adaptation Rather Than Its Substitute: A Narrative Review - Tryba, Michał; Paluch, Anna; Grylowska, Gabriela; Gunia, Katarzyna; Adamczyk, Aleksandra; Banasik, Mateusz; Rebizant, Marcin; Żak, Agata; Palak, Andrzej; Anna Ignatowicz (Quality in Sport, 2026)
Background. Xenon has been proposed as a potential agent influencing erythropoiesis through activation of hypoxia-inducible pathways. However, its role in high-altitude physiology and hypoxic adaptation remains unclear and controversial. Aim. This study aimed to evaluate whether xenon may act as a modulator of hypoxic adaptation rather than a substitute for hypoxic exposure. Material and methods. This study is a narrative literature review based on scientific publications indexed in the PubMed database between 1998 and 2025. The literature search included keywords such as xenon, hypoxia, HIF-1α, erythropoietin, hypoxic adaptation, and acclimatization. Original studies, review articles, and experimental studies investigating the physiological and molecular effects of xenon were included. Studies not related to hypoxia or adaptive physiological responses were excluded. Results. Available evidence indicates that xenon transiently increases erythropoietin levels via activation of the HIF pathway; however, these effects do not translate into sustained physiological adaptations such as increased hemoglobin mass or improved aerobic performance. Notably, most studies have evaluated xenon in isolation, without integration into complex adaptive conditions such as combined hypoxia and physical training. Conclusions. Xenon does not appear to substitute for hypoxic adaptation. Its potential role as a modulator of hypoxia-induced physiological responses remains insufficiently explored and requires further investigation within integrated experimental models.